Thermodynamic Analysis of Expansion Profile for Displacement-type Expander in Low-temperature Rankine Cycle - Mohd Tahir , Musthafah; Yamada , Noboru (The Japan Society of Mechanical Engineers and The Heat Transfer Society of Japan, 2010)
Thermodynamic analysis of the isentropic and polytropic expansion profiles of typical working fluids was carried out in order to design a highly efficient displacement-type expander for a low-temperature Rankine cycle. First, expansion profiles were analyzed for three typical working fluids: HFC245fa, ammonia, and supercritical CO 2. The hot-side temperature ranged from 60 ° to 120 °C, and the cold-side temperature was 10 °C. In the analysis, isentropic and polytropic expansion processes were assumed to behave thermodynamically. In the analysis results, we noted similarities among the expansion profiles for different hot-side temperatures. This similarity allowed us to introduce the unique concept of a variable mechanism for expansion profile fitting in displacement-type expanders. This variable expansion mechanism can be achieved by simply adjusting the position of the inlet and/or outlet port of the expander. © 2010 by JSME.